Comparison between monotherapy and combination therapy among inpatients with community-acquired pneumonia - Rike Syahniar; Audia Nizhma Nabila; Dayu Swasti Kharisma; Muhammad Afif Akbar (Universitas Islam Indonesia, 2021)
Background: Pneumonia causes high mortality, hospitalization costs and health services. There is some growing debate regarding the efficacy of different treatment management approaches. The use of certain antibiotic regimens combination and monotherapy have been associated with improved outcomes.Objective: This study aims to determine the effectiveness of monotherapy and combination therapy on length of stay.Method: This retrospective study included patients with Community Acquired Pneumonia (CAP) who received empirical therapy between January - December 2017 at Jakarta Islamic Hospital of Cempaka Putih. Two hundred and ninety four subjects were included in this study.Results: Subjects who received monotherapy and combination therapy were 73.8% and 26.2%. Mean length of stay was 5 days. The most widely used antibiotic in this study was ceftriaxone with levofloxacin (35%) for combination therapy and levofloxacin (38,2%) for monotherapy. There is a relationship between comorbidities and long-term hospitalization (p=0.008).Conclusion: There was no significant difference between combination therapy and monotherapy with length of stay (p=0.277).Keywords: Pneumonia, monotherapy, combination therapy, Jakarta Islamic Hospital of Cempaka PutihIntisariLatar belakang: Pneumonia menyebabkan tingginya angka kematian, biaya rawat inap dan pelayanan kesehatan. Terdapat beberapa perdebatan yang berkembang mengenai efikasi pendekatan manajemen pengobatan yang berbeda. Penggunaan kombinasi rejimen antibiotik tertentu dan monoterapi telah dikaitkan dengan hasil yang lebih baik.Tujuan: untuk menentukan efektivitas monoterapi dan terapi kombinasi terhadap lama rawatinap.Metode: Penelitian retrospektif ini melibatkan pasien dengan community acquired pneumonia yang menerima terapi empiris antara Januari - Desember 2017 di Rumah Sakit Islam Jakarta (RSIJ) Cempaka Putih.Hasil: Dua ratus sembilan puluh empat subjek dilibatkan dalam penelitian ini. Subyek yang menerima monoterapi dan terapi kombinasi sebesar 73,8% dan 26,2%. Rerata lama rawat inap pada kelompok monoterapi dan dualterapi yaitu 5 hari. Antibiotik yang paling banyak digunakan dalam penelitian ini yaitu seftriakson dengan levofloksasin (35%) untuk terapi kombinasi dan levofloksasin (38,2%) untuk monoterapi. Terdapat hubungan antara komorbid dengan lama rawat inap (p=0,008).Kesimpulan: Tidak terdapat perbedaan bermakna antara terapi kombinasi dan monoterapi dengan lama rawat inap (p=0,277)Kata kunci : Pneumonia, monoterapi, terapi kombinasi, RSIJ Cempaka Putih